Relationship between feminine writing and the construction of women's subjectivity in Li Tianbao's fiction - Chey, Zhen Cong (2021)
As gender research advances, the discussion in women's writing is more widespread. Feminine writing by women writers is one of the research topics. However, similar research on literary works by male writers is relatively rare. Essentially, feminine writing aims to expose women's subjectivity and focus on feminist discourse in literary studies. However, feminine writing does not belong exclusively to women but also includes male writers. The feminine writing by male writers is worthy studying further, especially concerning the writer's gender, writing styles, and feminist perspectives. Using the theory of feminism, this study aims to analyse the relationship between feminine writing in Li Tianbao's literary works and the construction of women's subjectivity in it. Firstly, the thesis will discuss Li Tianbao’s feminine writing on women's vital experiences in love, marriage and eroticism; and shows the unique life of a woman by subverting the dominating patriarchal discourse. Li Tianbao uses a dark and gloomy element in his feminine writing reveals the anxiety and depression of a woman characters living under the order of patriarchy. In addition, the thesis talks about women's living predicament through the reflection in the mirror and outside the mirror, while contemplating on the women’s reflection of self and the construction of self in an imagined world and analysing the method uses by Li Tianbao in constructing consciousness about women’s subjectivity in his works. The study found Li Tianbao in his literary works consciously presenting a woman’s world, through his understanding of gender and respect towards women from the aspect of constructing women’s subjectivity. In conclusion, Li Tianbao tries to disestablish the dominating patriarchal discourse. Using feminine writing, he uses women as the subject and exposed the hidden part of a woman’s world while at the same time constructing women’s subjectivity.